PERUBAHAN SOSIAL BUDAYA MUDA MUDI SIRULO BALI PADA ETNIK BATAK KARO DI KOTA DENPASAR - Sitepu, Bastanta; Punia, I Nengah; Kamajaya, Gede (JURNAL ILMIAH SOSIOLOGI (SOROT), 2018)
ABSTRACT Karonese is a part of Bataknese that inhabits in province of North Sumatra. Mudi Mudi Sirulo Bali (a name for community of Karonese youth that stay in Bali) is one of the organizations formed by Karonese located in Bali. This organization was formed to gather, know each other and learn about the culture together for Karonese youth in Bali. By the time in this developing era, some members of Mudi Sirulo Bali experience socio-cultural changes that lead to positive and negative impacts. The positive changes are that not all members of Mudi Mudi Sirulo Bali are from Tanah Karo, therefore they want to learn and preserve Karonese culture. Meanwhile, the negative changes are caused by western cultural that influences some of the members of Muda Mudi Sirulo Bali beginning to follow some their cultural lifestyles and forget the Karonese culture. The positive impact of this social change can cause Muda Mudi Sirulo Bali is able to be seen from the values ??and norms of Karonese that is now beginning to be preserved and upheld. The negative impacts could be seen from the changes of socio-cultural such as lifestyles, technological influences and lack of mutual respect among Mudi Mudi Sirulo Bali members in Bali. Keywords: social change, muda-mudi sirulo bali, culture, karo